Coastal Boundaries: Challenges and Law Enforcement On Hotel Services In Indonesia Tourism Areas - Bambang Karsono; Ika Dewi Sartika Saimima; Dwi Andayani Budisetyowati (Sociological Jurisprudence Journal, 2023)
As an archipelagic country, Indonesia has always been a tourist choice for travelers. Beach tourism is an option for tourists. In addition, the coastal area is one of the primary commodities of state income from the tourism sector. However, coastal areas often have problems related to control, ownership, use, or utilization of land. There are many violations of spatial planning, for example, making the object of the building a place of lodging around the shoreline. The development around the shoreline violates Article 17 of Law Number 33 concerning Job Creation which states that any person in carrying out his business and or activities utilizing the space that has been determined without having an agreement on the suitability of the use of space by causing a change in the function of the space will be punished with imprisonment for a maximum of 3 years and a fine, a maximum of 1 billion rupiahs. Presidential Regulation Number 51 of 2016 concerning Coastal Boundaries emphasizes the importance of establishing coastal boundaries. Preliminary observations of this problem indicate that there are still many buildings around the shoreline used as lodging, which results in abrasion of the coastal area. This study aims to discuss violations committed by hotels in tourism location, especially in the Kuta area. This study uses empirical normative legal research methods and studies of legislation that have not been effective. Law enforcement is needed to maximize the role of the government and society.